2009
DOI: 10.1007/bf03346485
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of glucose homeostasis and induction of insulin resistance by elevated free fatty acids in human L02 hepatocytes

Abstract: Free fatty acids (FFA) have been implicated as an important causative link between obesity, insulin resistance, and Type 2 diabetes. However, the underlying mechanisms especially for FFA-mediated hepatic insulin resistance are not fully elucidated. Here, we investigated the impaired sites in insulin signaling pathways and mechanisms of insulin resistance induced by elevated FFA in L02 hepatocytes. L02 cells were cultured in Dulbecco's modified eagle medium containing various concentrations of palmitic acid (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…A growing number of studies suggest that an important mechanism underlying this response is an increase in transcription of key gluconeogenic genes, particularly PCK1 and G6PC [26]. Increasing plasma FFA in rats increase hepatic G6PC mRNA abundance [28], and exposing primary hepatocytes to elevated FFA enhances mRNA abundance and the promoter activity of both PCK1 and G6PC [26,29], as well as PCK1 activity [30]. We found that exposing HepG2 and HuH7 cells to various concentrations of palmitate for 24 h significantly increased PCK1 and G6PC mRNA abundance in a dose-dependent manner; PCK1 promoter activity in HepG2 cells was increased twofold after a 24-h incubation in the presence of 1000 μM palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies suggest that an important mechanism underlying this response is an increase in transcription of key gluconeogenic genes, particularly PCK1 and G6PC [26]. Increasing plasma FFA in rats increase hepatic G6PC mRNA abundance [28], and exposing primary hepatocytes to elevated FFA enhances mRNA abundance and the promoter activity of both PCK1 and G6PC [26,29], as well as PCK1 activity [30]. We found that exposing HepG2 and HuH7 cells to various concentrations of palmitate for 24 h significantly increased PCK1 and G6PC mRNA abundance in a dose-dependent manner; PCK1 promoter activity in HepG2 cells was increased twofold after a 24-h incubation in the presence of 1000 μM palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of insulin to inhibit hepatic gluconeogenesis is to a large extent responsible for the disruption of glucose homeostasis and development of fasting hyperglycaemia [41]. PKB is a key molecule mediating the metabolic effect of insulin in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro IR models are mainly generated in hepatocytes, fat cells, and skeletal muscle cells using high concentrations of insulin; medium containing high levels of sugar and fat; dexamethasone; palmitic acid; and tunicamycin [26][27][28][29], although a high insulin concentration is most frequently used [30]. Dexamethasone, a kind of glucocorticoid, is easily confused with dexmedetomidine (owing to similar abbreviations), which induces IR by inhibiting the binding of insulin to the insulin receptor.…”
Section: Discussionmentioning
confidence: 99%